Pengaruh Kecemasan Karier dan Dukungan Sosial Terhadap Kepercayaan Diri Mencari Kerja Pada Fresh Graduate Dengan Regulasi Emosi Sebagai Variabel Permediasi - Saddam Jauhar Dliyaul Asyfa; Jati Waskito (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the effects of career anxiety and social support on job search self-efficacy among fresh graduates of the Faculty of Economics and Business, Universitas Muhammadiyah Surakarta (FEB UMS), graduating in 2023–2025, with emotion regulation serving as a mediating variable. This research employed a quantitative approach using a survey method. Data were collected through a closed-ended Likert-scale questionnaire administered to 110 respondents selected through purposive sampling. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The findings revealed that career anxiety had a negative and significant effect on both emotion regulation and job search self-efficacy. In contrast, social support had a positive and significant effect on emotion regulation and job search self-efficacy. Emotion regulation was also found to have a positive and significant effect on job search self-efficacy. Furthermore, emotion regulation partially mediated the effects of career anxiety and social support on job search self-efficacy. The research model explained 52.1% of the variance in job search self-efficacy. The implications of this study highlight the importance of strengthening career support services, enhancing social support, and providing emotion regulation training to improve the psychological readiness of fresh graduates in entering the labor market